Agency experience in children with typical development and children with autistic spectrum disorder - Carreras, Xilenia (2020)
Background: The Agency is capable of changing the own perceptual inputs at will (Russell, 1996;) 2000).The hypothesis of this work is that - according to Russell-, this would be altered in subjects with autism and that, on the other hand, it strengthens in critical periods of development (3 and 4 years old). Method: Assessed skills associated with the agency: monitoring of action, recognition of the Agency, instigation, the ability to correct errors on the fly and central inhibition, in children typical development of different ages, and children with and without autism using unpublished tests. Results: The differences due to age are found in the tests that evaluate the monitoring of an action plan, the recognition of the agency, the central inhibition and instigation, as well as the amount of mistakes made and the ability to correct them on the march. The differences between children with and without autism were found in the monitoring, instigation and ability to correct errors. Conclusion: These results show a progressive development of skills associated with the agency. In three-year-old children there are still difficulties in monitoring, instigating and inhibiting actions and in the recognition of the agency itself: skills that improve the following year and stabilize after 6 years. In children with autism, we found that the performance was different according to the clinical subtype, and that although there were alterations in the monitoring and instigation of the action (and according to the subtype, there were also differences in the control and correction of the error), they did not present difficulties in recognizing agency and central inhibition: central skills that are central to the management and control of one's own behavior as agents.